Bilateral anophthalmia with septo-optic dysplasia - Manisha Jana; Sanjay Sharma (Oman Journal of Ophthalmology, 2010)
Bilateral anophthalmia is a rare entity and association with septo-optic dysplasia is an even rare condition. The condition is characterized by absent eyeballs in the presence of eyelids, conjunctiva or lacrimal apparatus. Though anophthalmia can be diagnosed clinically, imaging plays a crucial role in delineating the associated anomalies. In addition, often clinical anophthalmia may prove to be severe microphthalmia on imaging. We describe the imaging findings in an infant with bilateral anophthalmia and septo-optic dysplasia.